Analisis Faktor yang Mempengaruhi Penerapan Keselamatan dan Kesehatan Kerja (K3) Pada Proyek Pembangunan Gedung di Atlantis Hills PT.Podorukun Nusantara - Andiman Promas Umbu Lele; Fifi Damayanti; Handika Setya Wijaya (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
The variables affecting this study are the implementation of Occupational Safety and Health (OSH) by PT. Podorukun Nusantara in the Atlantis Hills building construction project in Dau District, Malang Regency. OSH is very important for maintaining a safe workplace, preventing accidents, and increasing worker productivity and efficiency in the construction industry. Employees, managers, and project managers were the 55 respondents who received questionnaires as part of the quantitative methodology of this study. Using SPSS software, the collected data was then examined using multiple linear regression analysis, F and t tests, validity and reliability tests, and more. Safety management variables have a significant impact on OHS implementation, according to the data, but knowledge and implementation factors only partially show a meaningful impact. However, these three elements have a major impact on how well OHS is implemented overall. This study shows that active management participation in policy implementation, worker training, and supervision is crucial in fostering a safety culture in construction projects. It also helps businesses improve worker compliance and awareness of OHS implementation, which reduces workplace accidents.